STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN BUDAYA RELIGIUS - Lutfia Rahmah; Moch Bachrurrosyady Amrulloh (JP : JURNAL PENDIDIKAN, 2020)
Abstract: This article aims to describe the process of developing a religious culture in SMA Negeri 1 Kedungpring Lamongan as well as the outputs resulting from developing a religious culture as well as its supporting factors. Seeing the decline in adolescent morals is currently triggered by increasingly sophisticated technological developments, while morals are one of the goals of education to reduce the decline of teenagers' morals today and form students who have good morals to develop a school religious culture is one of the right solutions. This research uses a descriptive qualitative approach to the type of case study, the data obtained by the author from interviews, observation and documentation which are in the form of writing, words as well as field conditions which we then analyze so that they are structured. The results of this study are Islamic education teachers in collaboration with the school community to develop a religious culture. The culture that has developed is religious activities such as congregational prayers, infaq, S3 (smiles, greetings and greetings) these activities have succeeded in producing students with character. The strategies used by Islamic education teachers are 1. power strategy through prohibitions as well as orders 2. persuasive strategy through motivating, habituation, as well as exemplary. While the supporting factors are 1. Internal factors, namely the values that have been instilled by the predecessors, complete facilities as well as cooperation between school members and guardians of students; 2. External factors, namely students' different backgrounds.